Effect of vitamin C inhibiting liver fibrosis and lipid peroxidation in biliary obstruction of Wistar rats - ., Widhitomo; Usman, Nurhayat; Rudiman, Reno (International Surgery Journal, 2020)
Background: The aim of this study was to evaluate the potential inhibiting effects of vitamin C as an antioxidant against liver fibrosis and lipid peroxidation in the bile duct ligation- induced biliary obstruction of Wistar rats. Methods: A total of 25 male Wistar albino rats were divided into five groups: sham operated, control (bile duct ligation/BDL) without given vitamin C, BDL with vitamin C 75 mg, BDL with vitamin C 150 mg, and BDL with vitamin C 225 mg. Each group contained 5 animals. Vitamin C was given orally on day 3 after operation and after 14 days following vitamin C administration, all animals were performed laparotomy to obtain liver tissue samples for histopathological investigation of liver fibrosis and blood samples for malondialdehyde (MDA) as lipid peroxidation measurement. Results: The changes demonstrating hepatic fibrosis including moderate to markedly thickened wall of central veins, localized to diffuse perisinusoidal fibrosis, enlarged portal track, increased number of septa, and thickened width of septa were observed in BDL groups. MDA measurement were also observed in all groups. Treatment of biliary obstruction in BDL groups with vitamin C given orally attenuated liver damage. Both the MDA measurement and histopathologic investigation of hepatic fibrosis were observed to be reduced with the vitamin C treatment. Conclusions: Our data indicate that vitamin C inhibited liver fibrosis and lipid peroxidation in bile duct ligation-induced biliary obstruction of Wistar rats.